Consortia in Postsecondary Education - Konrad, Abram G.; Small, James M. (Canadian Journal of Higher Education, 1986)
This article presents the concept of consortia as formal collaborative arrange- ments between institutions, which are designed to enhance academic programs or other services provided. Forty years of experience in the United States are reviewed through the literature, and a synopsis of consortia in Canada is presented. From this review, some "pros and cons" of consortia are raised. Advantages include: reducing duplication, improving quality, increasing program diversity, increasing accessibility, financial advancement, improving communication and more effective planning and control. Cautions raised include: lack of trust, unequal commitment by members, undue emphasis on reducing costs, lack of clear expectations, mismatching membership and mission and irrelevant structure and theory. The authors conclude that the promise of consortia is such that more detailed study of Canadian consortia is warranted.